The Geopolitics of European Austerity: "Ordnungspolitik" and the German Economic Model’s Shadow over the Eurozone Crisis - Agnew, John (Geopolítica(s). Revista de estudios sobre espacio y poder, 2015)
Over the past five years two stories about the Eurozone crisis have dominated popular and academic accounts: (1) virtuous northern countries versus profligate southern ones and (2) a simple extension of the 2008-9 banking crisis into the Eurozone bond market. This paper proposes that the economic crisis is really a geopolitical one reflecting the mismatch between the normative model for the Eurozone based on German ideology and the reality of the Eurozone’s economic heterogeneity.
Keywords: policy paradigm; austerity; Eurozone; Ordnungspolitik; Germany